Smile or die: Can subjective well-being increase survival in the face of substantive health impairments? - Martin Binder; Guido Bünstorf (Philipps-University Marburg, School of Business and Economics, 2016)
A robust relationship between subjective well-being and mortality has been established in the literature. While this relationship has been confirmed for many measures and data sets, few studies address how it is affected by concrete diseases. In this paper we assess for the British Household Panel Survey (BHPS) data set from 1991-2008 how life satisfaction interacts with twelve concrete health impairments. Specifically, we analyze whether subjective well-being predicts longer survival in the panel for individuals having the respective impairments. We find that cancer, chest pains and diabetes consistently decrease survival in our sample, even controlling for the severity of health problems. But our results cast doubt on strong claims for the benefits of well-being on mortality: while life satisfaction generally predicts longer survival in the data set, this finding is not robust to controlling for the endogeneity of subjective well-being, and we do not find significant interactions between substantive health impairments and life satisfaction. Higher subjective well-being may keep you healthy, but once you have gotten sick, it does not predict your survival.
Keywords: I31; I12; C41; 330; subjective well-being; health; survival analysis; longevity; BHPS; life satisfaction